Purinergic and Cholinergic Drugs Mediate Hyperventilation in Zebrafish: Evidence from a Novel Chemical Screen - Rahbar, Saman; Pan, Wen; Jonz, Michael G. (PLOS ONE, 2016)
A rapid test to identify drugs that affect autonomic responses to hypoxia holds therapeutic and ecologic value. The zebrafish (Danio rerio) is a convenient animal model for investigating peripheral O2 chemoreceptors and respiratory reflexes in vertebrates; however, the neurotransmitters and receptors involved in this process are not adequately defined. The goals of the present study were to demonstrate purinergic and cholinergic control of the hyperventilatory response to hypoxia in zebrafish, and to develop a procedure for screening of neurochemicals that affect respiration. Zebrafish larvae were screened in multi-well plates for sensitivity to the cholinergic receptor agonist, nicotine, and antagonist, atropine; and to the purinergic receptor antagonists, suramin and A-317491. Nicotine increased ventilation frequency (fV) maximally at 100 μM (EC50 = 24.5 μM). Hypoxia elevated fV from 93.8 to 145.3 breaths min-1. Atropine reduced the hypoxic response only at 100 μM. Suramin and A-317491 maximally reduced fV at 50 μM (EC50 = 30.4 and 10.8 μM) and abolished the hyperventilatory response to hypoxia. Purinergic P2X3 receptors were identified in neurons and O2-chemosensory neuroepithelial cells of the gills using immunohistochemistry and confocal microscopy. These studies suggest a role for purinergic and nicotinic receptors in O2 sensing in fish and implicate ATP and acetylcholine in excitatory neurotransmission, as in the mammalian carotid body. We demonstrate a rapid approach for screening neuroactive chemicals in zebrafish with implications for respiratory medicine and carotid body disease in humans; as well as for preservation of aquatic ecosystems.